Priorities among effective clinical preventive services in British Columbia, Canada - Hans Krueger; Sylvia Robinson; Trevor Hancock; Richard Birtwhistle; Jane A. Buxton; Bonnie Henry; Jennifer Scarr; John J. Spinelli (BMC, 2022)
Abstract Background Despite the long-standing experience of rating the evidence for clinical preventive services, the delivery of effective clinical preventive services in Canada and elsewhere is less than optimal. We outline an approach used in British Columbia to assist in determining which effective clinical preventive services are worth doing. Methods We calculated the clinically preventable burden and cost-effectiveness for 28 clinical preventive services that received a 'strong or conditional (weak) recommendation for' by the Canadian Task Force on Preventive Health Care or an 'A' or 'B' rating by the United States Preventive Services Task Force. Clinically preventable burden is the total quality adjusted life years that could be gained if the clinical preventive services were delivered at recommended intervals to a British Columbia birth cohort of 40,000 individuals over the years of life that the service is recommended. Cost-effectiveness is the net cost per quality adjusted life year gained. Results Clinical preventive services with the highest population impact and best value for money include services that address tobacco use in adolescents and adults, exclusive breastfeeding, and screening for hypertension and other cardiovascular disease risk factors followed by appropriate pharmaceutical treatment. In addition, alcohol misuse screening and brief counseling, one-time screening for hepatitis C virus infection in British Columbia adults born between 1945 and 1965, and screening for type 2 diabetes approach these high-value clinical preventive services. Conclusions These results enable policy makers to say with some confidence what preventive manoeuvres are worth doing but further work is required to determine the best way to deliver these services to all those eligible and to establish what supportive services are required. After all, if a clinical preventive service is worth doing, it is worth doing well.